Potential Effects of Phenolic Compounds That Can Be Found in Olive Oil on Wound Healing - Melguizo-Rodríguez, Lucia (Foods, 2021)
The treatment of tissue damage produced by physical, chemical, or mechanical agents involves considerable direct and indirect costs to health care systems. Wound healing involves a series of molecular and cellular events aimed at repairing the defect in tissue integrity. These events can be favored by various natural agents, including the polyphenols in extra virgin olive oil (EVOO). The objective of this study was to review data on the potential effects of different phenolic compounds that can also be found in EVOO on wound healing and closure. Results of in vitro and animal studies demonstrate that polyphenols from different plant species, also present in EVOO, participate in different aspects of wound healing, accelerating this process through their anti-inflammatory, antioxidant, and antimicrobial properties and their stimulation of angiogenic activities required for granulation tissue formation and wound re-epithelialization. These results indicate the potential usefulness of EVOO phenolic compounds for wound treatment, either alone or in combination with other therapies. Human studies are warranted to verify this proposition.